2015
DOI: 10.5489/cuaj.2643
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary tuberculosis in North America: A rare clinical entity

Abstract: Introduction: Although tuberculosis (TB) is the most common cause of mortality from infectious diseases worldwide, genitourinary TB in North America is rare. We review 3 cases of genitourinary TB diagnosed within the last 5 years. Cases: The first case is that of a 76-year-old African-Canadian woman who was referred for percutaneous nephrolithotomy of right lower pole renal stones. Although renal TB was suspected, her initial urinary TB culture was negative. On follow-up imaging, she developed bilateral ureter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Urine culture gives the definitive diagnosis, taking up to 8 weeks to become positive and with up to 20% of false negative results 11. Molecular methods, as polymerase chain reaction (not done on our patient), give faster results and has been proved to be sensitive and specific, although some false negatives occur because of urinary inhibitory substances 6 10…”
Section: Discussionmentioning
confidence: 87%
“…Urine culture gives the definitive diagnosis, taking up to 8 weeks to become positive and with up to 20% of false negative results 11. Molecular methods, as polymerase chain reaction (not done on our patient), give faster results and has been proved to be sensitive and specific, although some false negatives occur because of urinary inhibitory substances 6 10…”
Section: Discussionmentioning
confidence: 87%
“…Our interest in this study originates from the following reasons. It has been found in clinical practice that chronic kidney disease (CKD) patients are susceptible infection to Mycobacterium tuberculosis due to reduced immune function of the patients, resulting in an infective complication of renal disease and tuberculosis, , and worse still, some CDK diseases and tuberculosis bear the correlation or may evolve into a complication. , The co-onset syndemic effects of renal disease and tuberculosis offer the potential requirements for novel drug combinations. Along this idea, we attempt to realize the cocrystallization of PRZ–FLA with some first-line antituberculosis drugs, such as rifampicin, isoniazid, and pyrazinamide, and meanwhile to assess the influences of cocrystallization modification on the slow-release profile of PRZ–FLA.…”
Section: Resultsmentioning
confidence: 99%
“…Our interest in this study originates from the following reasons. It has been found in clinical practice that chronic kidney disease (CKD) patients are susceptible infection to Mycobacterium tuberculosis due to reduced immune function of the patients, resulting in an infective complication of renal disease and tuberculosis, 41,42 and worse still, some CDK diseases and tuberculosis bear the correlation or may evolve into a complication. 43,44 The co-onset syndemic effects of renal disease and tuberculosis offer the potential requirements for novel drug combinations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This is the second most common form of extra-pulmonary tuberculosis after peripheral lymphadenopathy. 1 This study reported a rare case of genitourinary tuberculosis in 2-year-old Indonesia boy with malnutrition.…”
Section: Introductionmentioning
confidence: 88%